(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2016)
The moral of my story: the new always disturbs. The NCPC causes strangeness. There are dozens of books presenting the most varied interpretations. Some say that the code is dangerous for the judiciary, with judges already packing their bags for other countries (the United States and Rhodesia, I’ve been told at two congresses). Others are preparing the hermeneutic cow dribble, evading a more effective application. Article 489 is not made for Brazil, they say at congresses and symposiums. Where has there been a demand for detailed reasoning? There are those who propose deviant statements, as if the semantic limits of the new law were worthless. Just as the natives in the movie did, they go from the grater to the whistle. In short, since this is a law, it seems that those who are against the NCPC and, in particular, against the duty to state reasons, would like to elect a jurist to run to the edge of the world and discard the strange object. Yes, that strange object, the NCPC. Who would be chosen? Their task: to throw the NCPC into the solipsistic fog that covers the view of the horizon. I was also told that a native professor had an epiphany and came up with the following thesis: that the duty of coherence and integrity (article 926) is only a programmatic norm, without strict normativity. I’ll spare you the trouble of naming the author of this feat. Genius, no? Let’s all go to Stockholm to receive the Nobel Prize. In other words: the NCPC is a law that should not be obeyed. Why not? Because it is. And because it’s not "good" Oh well. The legislator would have "made a mistake". Others say that the removal of free conviction (article 371) means nothing. Another epistemic epiphany, isn’t it? I helped construct four provisions of the NCPC: 10 (no surprises), 371 (removal of free will), 926 (duty of jurisprudence to have coherence and integrity) and 489 (reasoning - minus the second paragraph which deals with weighting, of course). Here I’ll talk about the following: articles 926, 927, 371 and 489. And I’ll base the discussion on my theory of decision, which can be found in two of my books: Truth and Consensus1 and Constitutional Jurisdiction of Legal Decision. In it, I propose five principles (standards) that must be obeyed in every decision: preserving the autonomy of the law; hermeneutic control of constitutional interpretation; effective respect for the integrity and coherence of the law; the fundamental duty to justify decisions or how motivation is not equal to justification; the fundamental right to a constitutionally adequate response. Thus, I will try to work through the provisions of the CPC according to decision theory.